APLIKASI AUGMENTED REALITY (AR) DENAH RUMAH BERBASIS ANDROID - Kikim Mukiman; Rahmadi; Rizky Gunawan (POLITEKNIK PIKSI GANESHA, 2019)
The growth of the property business in Indonesia is increasing every year, but there are not many property developers in Indonesia who use Augmented Reality (AR) technology as a promotional media to market products, on average they still use two-dimensional brochures. Augmented Reality (AR) is a technology that combines two-dimensional and or three-dimensional virtual objects into a real three-dimensional environment and then projects these virtual objects in real time. Augmented Reality (AR) can package brochures as promotional media becomes more interesting and interactive. This paper describes how Augmented Reality (AR) is implemented in making a three-dimensional brochure design of Android Based Houses on Housing with Types 36/60 and 29/60. Augmented Reality (AR) is created using 3D objects using Blender software, the stage of exporting files, making markers, making background applications using CorelDraw software and the last stage of applying to Unity. By utilizing the technology of Augmented Reality (AR) in an interactive brochure, buyers can see the shape of the houses offered from various angles and buyers can better visualize the object of housing that will be selected by using an Android smartphone with a mobile that can be seen anywhere.